Comparative Outcomes of Paediatric Stroke in Supratentorial and Infratentorial Regions: A 12-Year Hospital-Based Study - Azita Tavassoli; Riahi, Aina; vafaeeshahi, Mohammad; Leila Tahernia; Ladan Afshar Khas; Maryam Kachuei (Iranian Journal of Child Neurology, 2025)
Objectives: The clinical outcomes of pediatric stroke in patients can vary significantly depending on the affected brain region. Supratentorial and infratentorial strokes may present different clinical features and prognoses. Understanding these differences is crucial for developing targeted treatment strategies and improving patient care. Accordingly, this study aimed to compare the outcomes of patients under 18 years old with supratentorial and infratentorial strokes. Materials & Methods: This retrospective cohort study included 100 children under 18 years old hospitalized due to stroke at Ali Asghar and Rasoul Akram hospitals from 2011 to 2023 and followed for 24 months. The motor and cognitive impairments were assessed 24 months post-stroke using the Modified Rankin Scale (MRS), the Bayley-III Scale (for children under three years), and the Binet scale (for children over three years). Statistical analyses were performed using T-tests and Chi-square tests. The required data include age, gender, stroke type (ischemic or hemorrhagic), stroke location (supratentorial /infratentorial), and underlying conditions. Results: The mean age of the patients was 70.47 months. About 57% of the patients were older than two years, and 67% were male. Supratentorial stroke was observed in 78% of cases. No significant difference was observed in age or gender distribution between the supratentorial and infratentorial groups (P = 0.64 and P = 0.128, respectively). Outcome comparisons between the groups revealed no significant difference in Binet scores; however, children with supratentorial strokes had significantly lower Bayley scores and higher MRS scores compared to the infratentorial group (P = 0.023 and P = 0.002, respectively). Conclusion: The present findings indicate that children with supratentorial strokes may experience more severe long-term motor and cognitive impairments. Further research is needed to investigate long-term outcomes in pediatric stroke patients based on stroke location